Environmental education in legislative texts through the Noble Qur’an, the Prophet’s Sunnah and current laws - A comparative study between the purposes of the texts and the means of activation - - Abderrahmane, Maidi (Journal of Science and Knowledge Horizons, 2022)
The issue of the environment or the ocean is still the focus of local and global attention and is the subject of study, awareness and regulation, due to the importance that is reflected in the issues of the environment and the dangers that threaten it, and it is the homeland of man in general. And the conditions of the city and the conditions of the industry in terms of energy generation and others, and how to benefit from waste diversion, and its positive or negative impact. That is why we find that it holds from time to time symposia, forums and lectures in order to study partial issues and what it contains of directives and activations to protect the human environment, which threatens it with dangers, There is no doubt that education and organization are a way to activate the mechanisms of environmental protection.